Adsorption of cobalt (II) octaethyIporphyrin and 2H-octaethylporphyrin on Ag(111): New insight into the surface coordinative bond - Bai, Yun; Buchner, Florian; Kellner, Ina; Schmid, Martin; Vollnhals, Florian; Steinrück, Hans-Peter; Marbach, Hubertus; Gottfried, Michael (New Journal of Physics, 2009)
The adsorption of cobalt (II) octaethylporphyrin (CoOEP) and 2H-octaethylporphyrin (2HOEP) on Ag(111) was investigated with scanning tunneling microscopy (STM) and photoelectron spectroscopy (XPS/UPS), in order to achieve a detailed mechanistic understanding of the surface chemical bond of coordinated metal ions. Previous studies of related systems, especially cobalt (II) tetraphenylporphyrin (CoTPP) on Ag(111), have revealed adsorptioninduced changes of the oxidation state of the Co ion and the appearance of a new valence state. These effects were attributed to a covalent interaction of the Co ion with the silver substrate. However, recent studies show that the porphyrin ligand of adsorbed CoTPP undergoes a pronounced saddle-shape distortion, which could alter the electronic structure and thus provide an alternative explanation for the new valence state previously attributed to the formation of a surface coordinative bond. With the octaethylporphyrins investigated here, which were found to adsorb in a flat, undistorted conformation on Ag(111), the effects of geometric distortion can be separated from those of the electronic interaction with the substrate. The CoOEP monolayer gives rise to an adsorption-induced shift of the Co 2p signal (-1.9 eV relative to the multilayer), a new valence state at 0.6 eV below the Fermi energy, and a work-function shift of -0.84eV (2HOEP: -0.44eV) relative to the clean surface. Comparison with data for the distorted CoTPP confirms the existence of a covalent ion-surface interaction that is insensitive to the conformation of the ligand. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.